2018
DOI: 10.1111/evo.13426
|View full text |Cite
|
Sign up to set email alerts
|

The “unguarded-X” and the genetic architecture of lifespan: Inbreeding results in a potentially maladaptive sex-specific reduction of female lifespan inDrosophila melanogaster

Abstract: Sex differences in ageing and lifespan are ubiquitous in nature. The "unguarded-X" hypothesis (UXh) suggests they may be partly due to the expression of recessive mutations in the hemizygous sex chromosomes of the heterogametic sex, which could help explain sex-specific ageing in a broad array of taxa. A prediction central to the UX hypothesis is that inbreeding will decrease the lifespan of the homogametic sex more than the heterogametic sex, because only in the former does inbreeding increase the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 64 publications
(147 reference statements)
0
34
0
Order By: Relevance
“…Despite its long history and intuitive appeal, our results suggest that the UXh may in fact not be a fundamental driver of sex-specific mortality. Since it was first formulated, more than three decades ago, support for the UXh has been scant and indirect [1, 9, 10, 12] and, while this may be due to the inherent difficulties in testing this hypothesis, there are also frequently overlooked reasons to doubt it plays a major role in explaining sex-specific lifespans. For example, the fact that there is likely to be strong selection against big effect X-linked recessive mutations in nature [22], meaning that any mutations that do accumulate on the recombining chromosome should have relatively minor effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its long history and intuitive appeal, our results suggest that the UXh may in fact not be a fundamental driver of sex-specific mortality. Since it was first formulated, more than three decades ago, support for the UXh has been scant and indirect [1, 9, 10, 12] and, while this may be due to the inherent difficulties in testing this hypothesis, there are also frequently overlooked reasons to doubt it plays a major role in explaining sex-specific lifespans. For example, the fact that there is likely to be strong selection against big effect X-linked recessive mutations in nature [22], meaning that any mutations that do accumulate on the recombining chromosome should have relatively minor effects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further shows that the heterogametic sex tends to exhibit higher mean/maximum lifespan across a wide taxonomic range, but phylogenetic signal and sexual selection could contribute to explain this relationship [10]. In addition, recent experimental evidence shows that “unguarding” the X chromosome in females erases the sex gap in lifespan in Drosophila melanogaster [11, 12] but see [13]. A second hypothesis focuses on the role of the heteromorphic Y (or W) chromosome.…”
Section: Mainmentioning
confidence: 99%
“…However, it is difficult to imagine how these effects could mediate female-specific responses in reproductive aging when condition is altered, especially here where we controlled for maternal effects. No support for the unguarded-X hypothesis was found in the most direct test of this hypothesis yet (Brengdahl et al 2018a), but more indirect tests have found patterns consistent with this possibility (Pipoly et al 2015;Carazo et al 2016;Sultanova et al 2018). In any case, it also seems difficult to construct a scenario where X-linked recessive mutations could cause a response in female but not male reproductive aging when condition is altered.…”
Section: Genetic Quality and Sex-specific Aging 767mentioning
confidence: 98%
“…Families that are exclusively self-compatible have lower net diversification rates than those that are predominantly self-incompatible (Ferrer and Good, 2012). Ostensibly selfing species having higher extinction rates than outcrossers (Wright et al, 2013) in part due to a reduced ability to adapt, especially to new environments (Hartfield et al, 2017).…”
Section: Why Wgd Are Not Followed By Immediate Diversification Thrustsmentioning
confidence: 99%